Proceedings of the 14th Annual Conference on Computer Graphics and Interactive Techniques 1987
DOI: 10.1145/37401.37427
|View full text |Cite
|
Sign up to set email alerts
|

Elastically deformable models

Abstract: The theory of elasticity describes deformable materials such as rubber, cloth, paper, and flexible metals. We employ elasticity theory to construct differential equations that model the behavior of non-rigid curves, surfaces, and solids as a function of time. Elastically deformable models are active: they respond in a natural way to applied forces, constraints, ambient media, and impenetrable obstacles. The models are fundamentally dynamic and realistic animation is created by numerically solving their underly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
648
0
3

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,061 publications
(652 citation statements)
references
References 21 publications
1
648
0
3
Order By: Relevance
“…3D physics-based simulation has had broad success in many modeling domains, and the work closest to ours involves chains (see, e.g., [Barzel and Barr(1988)]) and deformable objects (see, e.g., [Terzopoulos et al(1987)Terzopoulos, Platt, Barr, and Fleischer], [Terzopoulos and Witkin(1988)] Haptic interfaces have also been used to implement realistic 3D physics-based simulations (see [Baxter et al(2001)Baxter, Scheib, and Lin] and [Kim et al(2003)Kim, Sukhatme, and Desbrun]). …”
Section: Lifting In Four Dimensionsmentioning
confidence: 99%
“…3D physics-based simulation has had broad success in many modeling domains, and the work closest to ours involves chains (see, e.g., [Barzel and Barr(1988)]) and deformable objects (see, e.g., [Terzopoulos et al(1987)Terzopoulos, Platt, Barr, and Fleischer], [Terzopoulos and Witkin(1988)] Haptic interfaces have also been used to implement realistic 3D physics-based simulations (see [Baxter et al(2001)Baxter, Scheib, and Lin] and [Kim et al(2003)Kim, Sukhatme, and Desbrun]). …”
Section: Lifting In Four Dimensionsmentioning
confidence: 99%
“…The earlier approaches such as penalty method [2,27] and reaction constraint method [21,26] implemented collision response by altering the force matrix in the mass-spring method. In our simulations, we observed that the stability of the system was reduced when we applied penalty and constraint methods.…”
Section: Collision Responsementioning
confidence: 99%
“…D EFORMABLE models have been used in computer graphics for over twenty years, dating back to the early work of [1]- [3]. While our work will focus on massspring models, the main ideas should be extendable to finite element methods (such as those in [4] and [5]), though we do not evaluate FEMs within the scope of this paper.…”
Section: Introductionmentioning
confidence: 99%